Factors Associated with Timeliness of Hepatitis B Birth Dose: A Cross-sectional Study in North-Western Nigeria - Ibrahim, Olayinka Rasheed; Ibraheem, Rasheedat Mobolaji; Aliu, Rasaki; Lawal, Ibrahim Magaji (Folia Medica Indonesiana, 2022)
Highlights: • Uptake of hepatitis B birth dose vaccine within 24 hours of birth is low in Katsina, north-western Nigeria. • The most common reason for delay presentation for hepatitis B birth dose vaccine is maternal illness. Abstract: No studies focused on the hepatitis B birth dose (HepB-BD) vaccine since Nigeria adopted the strategy to reduce hepatitis B viral infection. Hence, we determined the uptake of HepB-BD, factors associated with timeliness, and those that contributed to delay. This study was a cross-sectional descriptive study carried out at an immunization post in north-western Nigeria. We recruited 400 mother-infant pairs that presented for the first immunization and obtained relevant information, including socio-demographics and reasons for the delays. Of the 400 infants, 44 (11.0%) received HepB-BD within 24 hours (timeliness), 105 (26.3%) and 274 (68.5%) by day 7 and 14, respectively. Multivariate analysis showed that mothers' education (primary adjusted odds (AOR) 17, 95% CI 1.404, 204.611), secondary AOR 5.9, 95% CI 1.148, 29.895), and tertiary AOR 7.7, 95% CI 1.228, 48.545), and third born AOR 8.2, 1.625, 41.018) were associated with HepB-BD timeliness. Maternal-related factors were the commonest (129; 46.6%) for delayed HepB-BD, with maternal illness the most commonly cited reason (37; 28.7%). This study showed a deficient level of uptake of HepB-BD vaccines among infants. Factors that were associated with timeliness included maternal education and higher birth order. The commonest reason for delayed HepB-BD was maternal illness.